ChemInform Abstract: One‐Step Chemoselective Conversion of Tetrahydropyranyl Ethers to Silyl‐Protected Alcohols. Issue 48 (2nd December 2014) - Bergueiro, Julian; Montenegro, Javier; Saa, Carlos; Lopez, Susana
Abstract The title reaction can also be to applied linear acetals (VII).